2019
DOI: 10.1007/s11676-019-00936-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre- and post-wildfire management practices on plant recovery after a wildfire in Northeast Iberian Peninsula

Abstract: Fire and pre-or post-fire management practices shape the distribution and richness of plant species. Here, the effects of pre-and post-fire management on vegetation recovery were studied at different times, up to 18 months after a wildfire. Two months after a 2015 wildfire, 18 study plots were established (three 4-m 2 plots for each treatment), vegetation regrowth was monitored and vegetal species richness (S), evenness (I T ), density (D), diversity (H 0 ) and maximum diversity (HMax) after 2, 10 and 18 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…Other studies, however, detected no or little effects on vegetation cover after post-fire treatments such as salvage logging and mulching (Fernández and Vega, 2016;Moya et al, 2020). Similarly, Francos et al, (2019), observed similar regrowth in non-treated stands and stands in which burned trees were either cut and manually removed or cut and left to the ground. Divergent vegetation responses are likely associated with the different forest types and species assemblages analysed in the studies above, most of which were performed in stands with P. pinaster or Pinus halepensis Mill.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Other studies, however, detected no or little effects on vegetation cover after post-fire treatments such as salvage logging and mulching (Fernández and Vega, 2016;Moya et al, 2020). Similarly, Francos et al, (2019), observed similar regrowth in non-treated stands and stands in which burned trees were either cut and manually removed or cut and left to the ground. Divergent vegetation responses are likely associated with the different forest types and species assemblages analysed in the studies above, most of which were performed in stands with P. pinaster or Pinus halepensis Mill.…”
Section: Discussionmentioning
confidence: 83%
“…However, the vegetation responses to active post-fire management of the burned biomass still remain unclear, despite that practices such as salvage logging, mulching and others are often carried out to facilitate plant resprouting and establishment of tree seedlings (Castro et al, 2011). In the Mediterranean region, many studies focused on the effects on soil conditions and tree regeneration in pine-dominated forests (Spanos et al, 2005;Castro et al, 2011;Francos et al, 2019;Moya et al, 2020), whereas relatively fewer investigations were conducted on plant community properties such as species composition and diversity (Leverkus et al, 2014;Fernández and Vega, 2016). Overall, it is still poorly understood how these variables are affected by the application of post-fire management in evergreen broadleaved forests of the Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…The same methods have been used in other post-fire vegetation recovery stu- dies to analyze the changes over time in small-scale fireaffected areas and with single inventories (Zheng et al 2018). The name and quantity of each species were surveyed and the vegetation inventory richness (S), diversity (H') and density (D) were measured following Francos et al (2020). S represents the number of plant species in each plot; evenness (It) is a measure of the relative abundance of the different species and D is the It/plot measure (in m 2 ).…”
Section: Study Area and Vegetation Inventorymentioning
confidence: 99%
“…Wildfires are a natural element in Mediterranean ecosystems (Keeley et al 2011). Many factors influence the evolution of soil properties as topography (Dillon et al 2011), fire intensity (Keeley 2009), post-fire weather conditions and forest management practices (Francos et al 2020). The combination of all of these factors results in fire severity.…”
Section: Introductionmentioning
confidence: 99%
“…Wildfires are a natural feature of ecosystem disturbance and their importance is recognised for vegetation dynamics (Moreno & Oechel, 1994; Lloret et al ., 1999; Paula & Pausas, 2008; Velle et al ., 2012). Most studies on post‐fire regeneration in Mediterranean ecosystems have focused on plants (Guo, 2001; Mitchell et al ., 2009; Marzano et al ., 2012; Schaffhauser et al ., 2012; Francos et al ., 2019). These studies have shown that plants have numerous strategies to survive, regenerate, and colonise after the fire (Lloret et al ., 1999), which include fire‐stimulated germination, or resprouting from stumps, lignotubers, or burls (James, 1984).…”
Section: Introductionmentioning
confidence: 99%